Gender and information technology : moving beyond access to co-create global partnership - Kirk, Mary, 1955- (Hershey, PA : Information Science Reference, 2009)
'This book explores the decline in female involvement in technology and other discrimination related to the industry'--Provided by publisher
'Premier reference source'--Cover
Includes bibliographical references and index
Keywords: High technology industries -- Employees; Sex discrimination against women